The effects of rainfall and sociality on host-parasite dynamics in the common mole-rat, Cryptomys hottentotus hottentotus (Lesson 1812) - Lutermann, Heike (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.